2005
DOI: 10.1007/s10534-005-3689-7
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and the Diabetic Heart

Abstract: Zinc (Zn) is an essential mineral that is required for various cellular functions. Its abnormal metabolism is related to certain disorders such as diabetic complications. Oxidative stress has been considered as the major causative factor for diabetic cardiomyopathy. Zn has a critical antioxidant action in protecting the heart from various oxidative stresses. Zn deficiency was found to be a risk factor for cardiac oxidative damage and supplementation with Zn provides a significant prevention of oxidative damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 67 publications
1
47
0
1
Order By: Relevance
“…There are many studies using experimental diabetic modeling and reporting increases in lipid peroxidation or changes in element metabolism in diabetic patients (Wilson et al 2003;Song et al 2005). Previous researchers have suggested an interrelationship between diabetes and various micronutrients, including Mg, Cr, Fe, Zn, Cu, etc.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies using experimental diabetic modeling and reporting increases in lipid peroxidation or changes in element metabolism in diabetic patients (Wilson et al 2003;Song et al 2005). Previous researchers have suggested an interrelationship between diabetes and various micronutrients, including Mg, Cr, Fe, Zn, Cu, etc.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a trial among diabetic patients, zinc supplementation was effective in reducing HbA1C. 7 Furthermore, some studies have suggested that zinc supplementation could improve insulin sensitivity in patients with non-insulin-dependent diabetes mellitus. 19 The national prevalence of MetS in Iran is high, and is estimated to be 34.7% among adults 20 and 14.2% among children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental and clinical studies have documented the fact that zinc deficiency may predispose to glucose intolerance, diabetes mellitus, insulin resistance, atherosclerosis and coronary artery disease. [7][8][9] The effect of zinc on low density lipoprotein-cholesterol (LDL-C) and high density lipoprotein-cholesterol (HDL-C) has also been reported. 7,10 Unlike the effects of macronutrients on MetS which have been extensively investigated, 1,10,11 the potential effects of micronutrients have received limited attention and such studies are particularly sparse in the pediatric age group.…”
Section: Anthropometric Measurement and Clinical Examinationmentioning
confidence: 99%
“…At the molecular level, Zn is an exceptionally important micronutrient, required for over 300 enzymatic reactions that take place in the body (79), and is part of more than 2000 Zn dependent transcription factors and other proteins (80). Zinc is present in the cell nucleus, nucleolus, and the chromosomes.…”
Section: Ilmentioning
confidence: 99%